2001
DOI: 10.1084/jem.193.8.935
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Chlamydial Protease–Like Activity Factor Responsible for the Degradation of Host Transcription Factors

Abstract: Microbial pathogens have been selected for the capacity to evade or manipulate host responses in order to survive after infection. Chlamydia, an obligate intracellular pathogen and the causative agent for many human diseases, can escape T lymphocyte immune recognition by degrading host transcription factors required for major histocompatibility complex (MHC) antigen expression. We have now identified a chlamydial protease– or proteasome–like activity factor (CPAF) that is secreted into the host cell cytosol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
540
2
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(569 citation statements)
references
References 22 publications
25
540
2
2
Order By: Relevance
“…Disruption of this component of the host cytoskeletal network has been postulated to allow the C. trachomatis vacuole to expand during infection. Proteolysis of several of these proteins has been attributed to the activity of CPAF (chlamydial proteasome-like activity factor), a Chlamydia protein that is secreted into the host cell cytosol (39,44). CPAF targets a wide variety host factors for degradation, and it is exciting to speculate that CPAF may also be responsible for the cyclin B1 cleavage observed in C. trachomatis-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of this component of the host cytoskeletal network has been postulated to allow the C. trachomatis vacuole to expand during infection. Proteolysis of several of these proteins has been attributed to the activity of CPAF (chlamydial proteasome-like activity factor), a Chlamydia protein that is secreted into the host cell cytosol (39,44). CPAF targets a wide variety host factors for degradation, and it is exciting to speculate that CPAF may also be responsible for the cyclin B1 cleavage observed in C. trachomatis-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on both our previous studies (16) and the present work, we hypothesize that chlamydiae may secrete factors into host cells for actively blocking host apoptosis pathways. Efforts are under way to identify the potential antiapoptotic factor(s) by using a combination of genetic selection and biochemical purification approaches (52) and to further understand the mechanisms of chlamydial antiapoptotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that chlamydia-laden vacuoles can actively avoid fusion with lysosomes, although the molecular mechanism involved remains to be elucidated (21,42). We have previously shown that chlamydiae possess various molecular means for protecting the infected cells from being destroyed by host defense mechanisms, including suppression of host cell major histocompatibility complex antigen expression (52)(53)(54) and blockade of host cell apoptosis pathways (16). However, due to the complex interactions between chlamydiae and host cells, different labs have reported varied outcomes in regard to chlamydial effects on the host apoptosis program.…”
mentioning
confidence: 99%
“…C. trachomatis has evolved mechanisms to evade CTL recognition and killing of infected cells through degrading the transcription factor RFX5, which is needed for constitutive and IFN-␥-induced MHC class I expression, leading to a severe drop of these molecules from the cell surface 24 h or later after infection (55,56). Despite this, CTL responses can be elicited against C. trachomatis-infected cells (57,58), presumably due to bacterial antigen processing and presentation early after infection.…”
Section: Discussionmentioning
confidence: 99%